Learning Processing : a beginner's guide to programming images, animation, and interaction - Shiffman, Daniel (Morgan Kaufmann series in computer graphics., 2008)
The free, open-source Processing programming language environment was created at MIT for people who want to develop images, animation, and sound. Based on the ubiquitous Java, it provides an alternative to daunting languages and expensive proprietary software. This book gives graphic designers, artists and illustrators of all stripes a jump start to working with processing by providing detailed information on the basic principles of programming with the language, followed by careful, step-by-step explanations of select advanced techniques. The author teaches computer graphics at.